STRATEGI PENGHULU DALAM PENCEGAHAN PERCERAIAN DINI PADA KANTOR URUSAN AGAMA KECAMATAN KATINGAN, KALIMANTAN TENGAH - Rusdiannor; Marzuki, Angga (Direktorat Jenderal Bimbingan Masyarakat Islam, 2018)
This research develops a strategy in preventing early divorce at the Religious Affairs office in Katingan Tengah Sub-district, Katingan Regency, Central Kalimantan Province. The results of this study are as follows; 1) the occurrence of early divorce in Katingan Tengah Sub-district is due to the absence of a spiritual relationship in the household life between a husband and wife while fostering a household because the husband is cheating, alcoholic drunkard, does not want to earn a living, there is a second intervention of their parents to their married child, changing religion (apostasy), the District Court decision against the husband with a verdict more than 5 (five) years in prison, not yet mature the thinking pattern in the family and wife does not carry out their obligations so that the husband and wife relationship is no longer hormonal. 2) provide pre-marriage, post-marriage counseling and carry out customary agreements that have been agreed upon 3) obstacles faced by the Moslem headman in preventing early divorce are do not want problems to be known by others. Psychological factors in the existence of domestic violence trauma. Penelitian ini mengembangkan Strategi dalam pencegahan perceraian dini pada Kantor Urusan Agama Kecamatan Katingan Tengah Kabupaten Katingan Provinsi Kalimantan Tengah. Hasil penelitian ini adalah sebagai berikut; 1) terjadinya percerai dini di Kecamatan Katingan Tengah disebabkan tidak adanya hubungan yang hurmonis dalam kehidupan rumah tangga antara seorang suami dan isteri selama membina rumah tangga dengan disebabkan suami selingkuh, pemabuk, tidak mau mencari nafkah, ada campur tangan kedua orang terhadap anaknya yang sudah menikah, pindah agama (murtad), adanya putusan Pengadilan Negeri terhadap suami dengan vonis diatas 5 (lima) tahun penjara, belum dewasanya pola berpikir dalam keluarga dan isteri tidak melaksanakan kewajibannya sehingga hubungan suami isteri tidak lagi hormonis. 2) memberikan penasihatan pra pernikahan, pasca pernikahan dan melaksankan perjanjia adat yang sudah disepakati 3) kendala yang dihadapi penghulu dalam pencegahan percerai dini adalah Tidak ingin masalah diketahui orang lain. Faktor psikologis adanya trauma kekerasan dalam rumah tangga